Influence of patch size on hydrodynamic flow in submerged aquatic vegetation - Matsumura, K.; Nakayama, K.; Matsumoto, H. (Frontiers in Marine Science, 2022)
Blue carbon, or carbon dioxide captured and stored by submerged aquatic vegetation (SAV) in ecosystems, has been attracting attention as a measure to mitigate climate change. Since the scale of SAV meadows is smaller than that of topography length scale, with the former often occurring in patches, the flexibilities of SAV motion induce complicated interactions with water flows and make it difficult to estimate carbon sequestration rates. Therefore, this study aims to clarify the influences of SAV patches on water flows and mass transport using laboratory experiments and numerical simulations. An SAV model was successfully applied to analyze the results of laboratory experiments, revealing good agreement and showing that the size of an SAV patch significantly affects the water flows. The extent to which the patch occupies the channel width was revealed to be the most substantial factor in controlling carbon absorption by SAV, and deflection was found to be another significant factor. Implementing global warming countermeasures is a critical goal of climate change mitigation, so our study outcome is expected to be helpful for improving and promoting blue carbon as a negative emission strategy.